PERAN PENGUSAHA PENGURUSAN JASA KEPABEANAN (PPJK) DALAM PROSES IMPOR BARANG BESERTA DOKUMEN YANG TERKAIT - Yusi Rahmawati; Uji Westi (Majalah Ilmiah Bahari Jogja, 2016)
This paper aims to understand the role of Customs Clearance Services Employers (PPJK), this paper is a descriptive article about PPJK Roles includes: the initial process of making PIB, the payment process through Online Billing system, the registration documents, and the Letter of Expenditure Approval (SPPB). The related documents are the Bill of Lading is issued letter explaining that the shipping company had received goods from shippers to be transported to the port destination and delivered to the recipient; Invoice is a type of document published or issued by exporter or supplier containing details of perhaps goods delivered concerning the quantity of goods, the type or name of goods, the price of goods, methods of delivery, and so on; and Packing list is details of goods in detail which contains the name of the Shipper, consignee, Notify Party, name of Vessel & Voyage, Dimension goods, Gross Weight and net Weight per item of goods as well as the overall total, amount of goods.